Rapid determination of emulsion stability by rheology-based thermal loop test - Tekin, Zeynep Hazal; Avci, Esra; Karasu, Salih; Toker, Omer Said (ELSEVIER, 2020)
This study aimed to determine the stability of oil-in-water emulsions using the thermal loop test as a novel method. Samples with xanthan gum concentrations of 0.1 g, 0.2 g, 0.3 g, 0.4 g or 0.5 g/100 g were subjected to 10 thermal cycles from 5 to 23 degrees C (low-temperature stability test) and 23-45 degrees C (high-temperature stability test). In the low-temperature stability test, the relative change of G* for the samples (Delta) was 4.15%, 2.82%, 1.32%, 1.17%, and 4.68%, respectively. In the high-temperature stability test, the Delta values were 7.7%, 0.58%, and 7.22% for samples 3-5, respectively. However, samples 1 and 2 had dramatic changes in G*. This was also confirmed by a visual test, zeta potential measurement, polydispersity index, and particle size distribution. Moreover, a low zeta potential, high polydispersity indexes, and phase separations yielded high Delta values. This study implies that the thermal loop test could be successfully applied to determine the emulsion stability in food emulsions.
Keywords: Zeta potential; Rheology; Physical stability; Thermal loop test; Xanthan gum; MICROSTRUCTURE; AGGREGATION; DRESSINGS; Food Science & Technology